Jerilderie : 100 years. - Jerilderie (N.S.W. : Shire). Council ([Jerilderie, N.S.W., 1958)
History of Jerilderie, NSW, and recollections of the Kelly raid. Reference to local Aboriginal population p. 12.
- History of Jerilderie: by H. C. Lundey. - The Kelly raid on Jerilderie: by "One who was there".
cover-title.
Previously published in serial form in the Jerilderie Herald, 1950 and 1913.
Keywords: Settlement and contacts - Colonisation; Race relations; Jerilderie (SW NSW SI55-14)